2019
DOI: 10.1111/1759-7714.13278
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Rab17 promotes cell proliferation and invasion in non‐small cell lung cancer through STAT3/HIF‐1α/VEGF signaling

Abstract: Background: Rab GTPases play a key role in regulating intercellular vesicle trafficking in both exo-and endocytic pathways. Recent studies have reported that Rab small GTPases and the associated regulatory proteins and effectors are involved in many cancers. The purpose of this study was to investigate the biological role of Rab17 in non-small cell lung cancer (NSCLC) and the relative mechanism. Methods: Rab17 expression in human NSCLC cell lines and tissues was evaluated using real-time PCR (RT-PCR), western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…32,34 More importantly, some recent studies have revealed that the STAT3/ HIF-1α/VEGF pathway was activated in NSCLC. 11,12,35 The relationship between STAT3 expression and apoptosis had been reported in many studies. Generally, while the expression, production, phosphorylation, or activation of STAT3 was found in various cancer cells, the apoptosis process in these cells was inhibited.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…32,34 More importantly, some recent studies have revealed that the STAT3/ HIF-1α/VEGF pathway was activated in NSCLC. 11,12,35 The relationship between STAT3 expression and apoptosis had been reported in many studies. Generally, while the expression, production, phosphorylation, or activation of STAT3 was found in various cancer cells, the apoptosis process in these cells was inhibited.…”
Section: Discussionmentioning
confidence: 97%
“…6 It has been reported that the STAT3/HIF-1α/VEGF pathway was closely associated with tumorigenesis and progress of various tumors, including hepatocellular carcinoma, gastroenteropancreatic neuroendocrine tumor, hemangioma, malignant peripheral nerve sheath tumor, and NSCLC. 7,12 Resveratrol (trans-3,4′,5-trihydroxystilbene, RES), a natural polyphenolic compound, is found in a large number of edible plants, especially grapes and peanuts. 13 Numerous studies have demonstrated its diverse pharmacological activities, such as immune regulation, neuroprotection, antioxidant and anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HIF-1α enhances the invasion and migration of OC cells induced by hypoxia ( 33 ). Interestingly, STAT3 promotes the expression of HIF-1α as its upstream molecule ( 17 , 34 ). Here, we found that overexpressing DSCR8 greatly promoted the activation of STAT3/HIF-1α, while overexpressing miR-98-5p reduced STAT3 expression and activation, indicating that DSCR8/miR-98-5p regulates OC development by regulating STAT3/HIF-1α pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that miRNA cluster MC-let-7a-1∼let-7d regulates glioma autophagy and apoptosis by targeting STAT3 ( 16 ). Besides, hypoxia inducible factor 1 alpha (HIF-1α), a prime modulator of cellular and systemic homeostatic response to hypoxia, can be activated by STAT3 and then regulate tumorigenesis ( 17 ). Here, our previous study demonstrates that lncRNA DSCR8 is upregulated in OC.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the role of RABs in the shedding of extracellular vesicles has also been reported [ 55 , 56 , 57 , 58 ]. Aberrant expression of RABs is reported in various cancers, and they are shown to act either as a tumor promoter or suppressor in a context-dependent manner [ 59 , 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%